Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T17:23:36+01:00
X/6-1/6=1 /*6
x-1=6
x=7

-2(2x-1)=x/3
-4x+2=x/3 /*3
-12x+6=x
-13x=-6
x=6/13

2/5(3-x)=-2
6/5-2/5x=-2 /*5
6-2x=-10
-2x=-16
x=8

3/4(2-3x)=-6
6/4-9/4x=-6 /*4
6-9x=-24
30=9x
x=30/9

1/5(x-3)=9-x
1/5x-3/5=9-x /*5
x-3=45-5x
-4x=45+3
-4x=48
x=-12






2010-03-02T17:28:51+01:00
X/6 - ⅙ = 1 /*6
x - 1 = 6
x = 7

-2(2x-1) = x/3
-4x + 2 = x/3 /*3
-12x + 6 = x
-12x - x = -6
-13x = -6/:(-13)
x = ⁶/₁₃

⅖(3-x) = -2
1⅕ - ⅖x = -2
1⅕ + 2 = ⅖x
3⅕ = ⅖x /:⅖
8 = x

¾(2-3x) = -6
1½ - 2¼x = -6
7½ = 2¼x /:2¼
3⅓ = x

⅕(x-3) = 9-x
⅕x - ⅗ = 9 - x
1⅕x = 9⅗ /:1⅕
x = 8

0,6 = x/2 = x = 1
To równanie to chyba źle przepisałaś, bo są 3 znaki =

;-))